Evidence-based first aid and prevention guidelines for lay people in India - Buck, Emmy De; Remoortel, Hans Van; Geuvens, Hugo; Veegaete, Axel Vande; Singhal, Maneesh; Vandekerckhove, Philippe; Agarwal, Satya Paul (Indian Journal of Community Health, 2015)
Background: Training first medical responders is considered an extremely cost-effective intervention for frequently occurring diseases and injuries in low and middle-income countries. Aims & Objectives: The Belgian Red Cross-Flanders together with the Indian Red Cross Society, aimed to develop evidence-based guidelines to train lay people on how to manage and prevent emergency situations in India. Methods: Evidence-based guidelines were developed adhering to the principles of AGREE II. The reporting of the systematic literature reviews was done according to the PRISMA statements. We identified evidence on the effectiveness of various first aid and preventive procedures from Indian studies and on alternative interventions that have been used by Indian laypeople. The quality of the scientific evidence was determined using the GRADE methodology. Values and preferences from the target group were collected and inputs from a multidisciplinary panel of 12 Indian experts were taken. Result: After developing 77 specific search strategies in PubMed, 10055 references were screened and 90 relevant studies were included as a basis for the recommendations in the guidelines. Examples of effective interventions include rice water for diarrhoea, and gargling to prevent respiratory infections. Conclusion: Evidence-based first aid and prevention guidelines for Indian laypeople were developed. These guidelines will increase the capacity of the Indian Red Cross Society in providing appropriate first aid training and first aid information to the public, and in delivering first aid assistance in case of disasters, disease outbreaks, emergencies, and road accidents in India.